PGE2-EP2/EP4 signaling elicits immunosuppression by driving the mregDC-Treg axis in inflammatory tumor microenvironment - Dean Thumkeo (2022)
Active inflammation generally promotes immune activation. However, in the tumor microenvironment (TME), active inflammation occurs in parallel with immunosuppression, and both contribute to tumor growth. Why inflammation does not lead to immune activation in TME remains unclear. In this study, using the immune checkpoint inhibitor-insensitive mouse cancer model and single-cell RNA sequencing, we show that PGE2-EP2/EP4 signaling simultaneously promotes active inflammation by inducing expression of the NF-κB genes in myeloid cells and elicits immunosuppression by driving the mregDC (mature DC enriched in immunoregulatory molecules)-Treg (regulatory T cell) axis for Treg recruitment and activation in the tumor. Importantly, the EP2/EP4 expression level is strongly correlated with the gene signatures of both active inflammation and the mregDC-Treg axis and has significant prognosis value in various human cancers. Thus, PGE2-EP2/EP4 signaling functions as the key regulatory node linking active inflammation and immunosuppression in TME, which can be targeted by EP2 and EP4 antagonists for cancer therapeutics.